EARLY INTERVENTION IN PREGNANT WOMEN THROUGH NUTRITION EDUCATION AND ANTENATAL CARE MONITORING TO PREVENT STUNTING - Devi Nuraini Santi; Evawany Yunita Aritonang; Mauly Purba (Universitas Airlangga, 2026)
Introduction: Maternal and infant mortality in Indonesia remain high, largely due to anemia in pregnancy, which increases the risk of childhood stunting. Ensuring balanced nutrition and optimal antenatal care (ANC) is essential for prevention. This study aimed to enhance pregnant women’s nutritional knowledge and ANC compliance through education and monitoring. Methods: A community-based intervention was conducted through training, mentoring, and monitoring activities involving primary health care staff and pregnant women. Key indicators included hemoglobin (Hb) status, iron–folic acid (IFA) supplementation adherence, and compliance with trimester-based ANC visits. Data were analyzed using descriptive quantitative methods and comparative proportion analysis across pregnancy trimesters. Results: Among 19 pregnant women who underwent Hb testing, 73.7% had normal Hb levels, while 26.3% were anemic. IFA adherence reached 100% in the first and second trimesters but declined sharply to 28.5% in the third trimester. Similarly, full-standard ANC coverage was achieved in the first trimester and decreased progressively in later trimesters. These proportional differences highlight critical gaps in late-pregnancy care despite early intervention. Conclusion: Structured nutrition education and ANC monitoring improved knowledge, supplementation adherence, and pregnancy care quality. Early intervention may reduce anemia prevalence and stunting risk. KEYWORDS antenatal care; anemia; nutrition education; pregnant women; stunting